Iklim Komunikasi Berbasis Kearifan Lokal Studi Kasus Di Pusat Pelatihan Dan Pengembangan Dan Pemetaan Kompetensi Aparatur Sipil Negara LAN-RI Jatinangor - Restie Almha; Wawan Setiawan Abdillah; Khaerul Umam (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
This journal discusses the climate of communication of local wisdom-based organizations in Puslatbang PKASN LAN-RI Jatinangor. Especially the application of the value of local wisdom in the organizational communication climate at the PKATN LAN-RI Jatinangor Puslatbang. The purpose of this research is to find out how Climate Communication of Local Wisdom-based Organizations in PKlatN LAN-RI Jatinangor, to find out the barriers that occur in the climate of communication of local wisdom-based organizations in PKlatN LAN-RI Jatinangor, and find out the efforts made to overcome obstacles in climate communication of local wisdom-based organizations at the PKATN LAN-RI Jatinangor Puslatbang. The study was conducted using the case study method with a qualitative approach. Data collection techniques using interview techniques and study documentation. The results of this study are that the climate of organizational communication based on local wisdom is not yet optimal in terms of the delivery of written information that is difficult for members to understand. And the lack of attention to ethics and valuesthat apply, especially in the achievement of ideas, ideas or information.